Waste management techniques for improved environmental and public health : emerging research and opportunities - Tsai, Sang-Bing, 1973- (Engineering Science Reference (an imprint of IGI Global), 2020)
""This book provides insights into the advancing methods and technologies of reducing pollution and promoting sustainable development. It also examines ecological technologies, risk assessment, and green operation"--Provided by publisher"-- Provided by publisher.
Keywords: Refuse and refuse disposal.; Environmental health -- Economic aspects.; Sustainable development.; Public health -- China.; Green technology.; elektronické knihy; electronic books